Мініатюрні постійні магніти на базі сплаву Nd-Fe-B, отримані методом інтенсивної деформації - Бовда, О.М.; Бовда, В.О.; Кошкарьов, Г.С.; Онищенко, Л.В.; Тортіка, О.С. (Вопросы атомной науки и техники, 2009)
Інтенсивна деформація швидкозагартованих магнітних сплавів може стати принципово новим шляхом
отримання тонких магнітів з високими магнітними властивостями. Досліджено структуру та магнітні властивості деформованого швидкозагартованого магнітного сплавуNd₁₃,₅Fe₇₃,₃Co₆,₇Ga₀,₅B₆. Встановлено, що деформація сплаву відбувається не лише за рахунок фрагментації вихідного порошку, а також супроводжується структурно-фазовими перетвореннями. Термічна обробка веде до появи двофазної поведінки кривої
розмагнічування. Severe deformation of melt-spun magnetic alloys can be a principally a new way for obtaining thin magnets with
high magnetic performance. The aim of this paper was to study structure and magnetic properties of deformed
Nd₁₃,₅Fe₇₃,₃Co₆,₇Ga₀,₅B₆. melt-spun alloy. It was shown that deformation is not only due fragmentation of the initial
powder, but accompanied by the phase and structure transformations. Heat treatment leads to the appearance of twophase
behaviour of demagnetisation curve. Severe deformation of melt-spun magnetic alloys can be a principally a new way for obtaining thin magnets with
high magnetic performance. The aim of this paper was to study structure and magnetic properties of deformed
Nd₁₃,₅Fe₇₃,₃Co₆,₇Ga₀,₅B₆ melt-spun alloy. It was shown that deformation is not only due fragmentation of the initial
powder, but accompanied by the phase and structure transformations. Heat treatment leads to the appearance of twophase
behaviour of demagnetisation curve.